A study of unsteady hydrodynamic effects in the stern area of river cruisers in shallow water. Issue 2 (4th May 2017) - Shevchuk, Ivan; Kornev, Nikolai
ABSTRACT: The aim of the presented research was to determine, how the fairway depth restriction can influence the hydrodynamic exciters of ship stern vibration. A series of computations of the flow around the inland cruise ship was conducted using the hybrid URANS/LES turbulence modelling methods in conjunction with the synthetic turbulence generation. The computational method was tested for the prediction of the wake of an inland ship in model scale and afterwards applied for a typical river cruiser geometry. A range of the depth-to-draft ratios and the drift angles was studied. The flow around the cruise ship was simulated both with and without propulsors. Based on the simulations, the statistical analysis of the longitudinal velocity field in the propeller plane, thrust fluctuations and pressure pulses on the hull was performed. It was shown that all the hydrodynamic sources of stern vibration are intensified when the ship enters the restricted waters. Under certain conditions, the velocity fluctuations can reach 25% of the ship speed, the thrust fluctuations can be as high as 6.5% of the mean and the amplitude of the pressure pulses can increase to 8 kPa. Analysis of the cavitation inception regions showed that the risk of cavitation can increase in shallow water. Abbreviations: CFD: computational fluid dynamics; (U)RANS: (Unsteady) Reynolds-Averaged Navier–Stokes; LES: Large-Eddy Simulation; SST: shear stress transport; IDDES: improved delayed detached Eddy simulation; SIMPLE: semi-implicit method for pressure-linked equations; PISO: pressure-implicit with splitting of operator; TVD: total variation diminishing; EDF: empirical distribution function